Analysis on the bending deformation characteristic and crack failure mechanism of thin-walled stainless-steel bellows. (January 2023) - Yan, Meng; Wang, Meng-ye; Xu, Zhi-fan; Liu, Yong; Chen, Lei; Huang, Hua-gui
Highlights: Larger variation in stress and wall thickness make the wave valley easy to fracture. The grain size and grain uniformity affect the bending resistance of the trough. Bending resistance of bellows is related to the content of low angle grain boundary. Fracture morphology of bellows changes with the optimization of matrix structure. Grain refinement in the trough region makes secondary cracks narrow and serrated. Abstract: In view of the fact that the small-diameter thin-walled stainless-steel bellows are easy to break at the trough and have a vague failure mechanism, this paper adopts the method of combining finite element simulation, bending experiment, and microscopic characterization to conduct a detailed study on the bending deformation characteristic and fracture failure mechanism of bellows. Results show that the repeated bending deformation process of the bellows is a reciprocal loading/unloading process, in which the amplitude of plastic stress gradually increases, and the amplitude of stress change in the trough is significantly higher than the peak. The large variations in stress and wall thickness are found to be major factors in the fracture of the trough. Due to the influence of molding and heat treatment processes, the microstructure differences are the internal causes for the fracture of the trough, such as the larger grain size, the insufficient uniformity of grain and the higher content of martensitic phase ratio. The Analysis on crack failure mechanism shows that the refinement and homogenization of grain could change the fracture morphology of bellows from quasi-dissociation fracture to ductile fracture, the secondary cracks become thinner and more numerous, and the crack boundaries change from straight to serrated, which significantly reduces the crack expansion rate and improves the bending resistance of bellows.